Exploring organizational culture, quality assurance, and performance in higher education - Idris, Idris (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This study aims to examine the relationship between organizational culture, quality assurance, and organizational performance, and test the quality assurance can be a mediator in their relationship. The research design uses quantitative methods using a questionnaire instrument. The sample is determined based on the Slovin formula. Data were analyzed using Partial Least Square (PLS). This research found that organizational culture can influence organizational performance and quality assurance. Also, quality assurance influences organizational performance positively and significantly. The mediation testing found that quality assurance can positively and significantly be a mediator in the relationship between organizational culture and organizational performance. This research indicates that the organizational culture climate has a very strategic role in driving the performance and implementation of the organization's quality assurance in higher education.